Determinants of User Satisfaction and Net Benefits of Electronic Medical Record Information Systems in Eastern Military Hospitals - Aldy Fitrah Bramantio; Merita Arini (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2026)
The rapid digital transformation in healthcare has accelerated the adoption of Electronic Medical Records (EMR) to improve service quality, data management, and patient safety. However, despite national policies mandating EMR implementation in Indonesia, adoption remains uneven across healthcare facilities, particularly in regions with limited digital infrastructure and technological readiness. Hospitals in eastern Indonesia face challenges such as unstable internet connectivity, limited technological resources, and varying levels of digital literacy, which may reduce the effectiveness and benefits of EMR implementation. This study aims to analyze the influence of system quality, information quality, and service quality on user satisfaction and the net benefits of EMR implementation using the DeLone and McLean Information System Success Model. A quantitative cross-sectional design was employed using survey data collected from 84 EMR users at Tk. III J.A. Dimara Hospital, Manokwari. Total sampling was applied to include all active EMR users who met the inclusion criteria. Data were analyzed using SmartPLS 4.0 software with Partial Least Squares Structural Equation Modeling (PLS-SEM). Statistical significance was determined using a two-tailed test with a critical t-value > 1.96 and p < 0.05 at the 95% confidence level. The results indicate moderate explanatory power, with R² values of 0.534 for system use, 0.638 for user satisfaction, and 0.578 for net benefits. Seven out of nine hypotheses were supported. System quality and information quality significantly influence system use, while information quality and service quality significantly influence user satisfaction. However, system quality does not significantly affect user satisfaction, and service quality does not significantly affect system use. Furthermore, system use and user satisfaction significantly contribute to net benefits, with user satisfaction demonstrating the strongest effect. These findings suggest that improving information quality, service support, and effective system utilization is essential for enhancing EMR performance and achieving meaningful organizational benefits in hospital settings